Effect of fluxing agents on reduction degradation behaviour of hematite pellets. (15th March 2016) - Dwarapudi, S.; Sekhar, C.; Paul, I.; Prasad, Y. G. S.; Modi, K.; Chakraborty, U.
Abstract : During induration at a high temperature, a considerable amount of slag/melt phase forms inside the iron ore pellets, comprising SiO2, Al2 O3, CaO, MgO and FeO. After cooling, the slag phase solidifies and acts as an important bonding phase in the finished pellets and influences their room temperature as well as high temperature properties, especially reduction degradation. Fluxing agents play an important role in forming these bonding phases depending on the type and amount of flux. In the present study, the effect of different fluxing agents, namely, limestone, dolomite, magnesite and pyroxenite, on melt formation and microstructure during induration and on reduction degradation behaviour during reduction was examined. From the results, it was understood that to reduce the disintegration during reduction it is essential to increase the amount and distribution of bonding phases like silicates, which are more stable as compared to oxide phases like hematite. Acid pellets exhibited highest reduction degradation due to the presence of more hematite bonds and less silicate bonds. In limestone fluxed pellets, reduction degradation index dropped considerably with increasing CaO content due to the formation of more amount of bonding phase. Dolomite–pyroxenite pellets, on the other hand, showed lower reduction degradation index up to 0.4 basicity, and beyond that, higher degradation was observed due to the increased pore size, which resulted in poor strength of the reduced pellet matrix and hence more degradation. Low reduction degradation observed in pyroxenite and magnesite fluxed pellets could be due to the formation of magnesioferrite and silicate melt, which are more stable phases compared to hematite.